Kinematic characteristics of gait with different myopia: a cross-sectional study - Xue, Aochuan; Zeng, Zhaohong; Wang, Huihui; Han, Jinming; Pang, Bo (Frontiers in Public Health, 2023)
Background Myopia, a condition affecting approximately one-quarter of the world' s population, has been projected to double in prevalence by the year 2050. It can have an impact on postural control during walking and can increase the risk of falls and injuries. Objective (1) To examine the abnormal performance of postural control during walking in male college students who used convex lenses for myopia intervention from a kinematic perspective; (2) to establish theoretical foundation for preventing falls and injuries in the myopic population. Methods A total of 22 male college students participated in this study. The center of gravity (COG), the percentage of gait cycle (PGC) and the joint angle(JT) were collected as indications of postural control during walking. A quantitative analysis was conducted using a One-Way Repeated Measures ANOVA to examine the variations among the three groups. Results During myopic interventions, (1) the range of vertical COG changes is significant to be greater compared with normal vision (P < 0.05). (2) there was an significant increase in the PGC in single-legged support, accompanied by a decrease in the PGC in double-legged support, compared with normal vision (P < 0.05). (3) The myopic intervention leads to increased variability in JT of the hip and the knee during the single-leg support and swing, as compared to individuals with normal vision (P < 0.05). Severe myopic interventions result in more changes in JT of ankle. Conclusion Myopia has been found to have a negative impact on postural control during walking, leading to changes in balance, increased instability, and an elevated risk of injury.